Digital Branding as an Effort to Advance Micro, Small, and Medium Enterprises (MSMEs) in Kademangan Sub-District - Eko Wahyono; Munawaroh; Khoridatil Bahiyah; Mohammad Fryo Dharma Saputra; Moch. Rizqy; Adella Pramesti Ekaditya Rohman; Tarisa Rohmaniah Putri; Moh Rosidi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Micro, Small and Medium Enterprises (MSMEs) in Kademangan Village, Probolinggo City, East Java, have not yet fully developed. This is due to a lack of knowledge and understanding about the importance of brands and digital branding. MSMEs in Kademangan Village only focus on production and sales, without understanding the importance of digital branding for a business. As we know, MSMEs are one of the backbones of the country's economy so assistance is needed to develop and advance them. This community service aims to increase knowledge and understanding of MSMEs in Kademangan Village about the importance of digital branding. The methods used include socialization, assistance and guidance for MSME actors in Kademangan Village. The results of the activity show an increase in MSME players' understanding of branding and how to market products via social media.